2001
DOI: 10.1159/000046071
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric Oxide Synthase Intron 4 Polymorphism Influences the Progression of Renal Disease

Abstract: Background/Aim: Nitric oxide is a potent regulator of intrarenal hemodynamics and may influence the renal function. We investigated whether polymorphism of intron 4 of the endothelial constitutive nitric oxide synthase (ecNOS) gene is related to the progression of chronic renal failure. Methods: Polymorphism of ecNOS intron 4 was studied in 1,005 hemodialysis patients (710 with nondiabetic nephropathy and 295 with diabetic nephropathy) and was compared with the findings in 189 healthy subjects. ecNOS genotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 16 publications
3
26
1
Order By: Relevance
“…Recent studies have reported an association between eNOS polymorphisms that lead to decreased eNOS expression and development of advanced nephropathy in patients with type 1 (199 -201) and type 2 diabetes (202,203). Other studies have found an association of these polymorphisms with ESRD (204,205). However, not all studies have detected any potential association of these eNOS polymorphisms with DN (206 -210).…”
Section: Endothelial Nitric Oxide Synthasementioning
confidence: 99%
“…Recent studies have reported an association between eNOS polymorphisms that lead to decreased eNOS expression and development of advanced nephropathy in patients with type 1 (199 -201) and type 2 diabetes (202,203). Other studies have found an association of these polymorphisms with ESRD (204,205). However, not all studies have detected any potential association of these eNOS polymorphisms with DN (206 -210).…”
Section: Endothelial Nitric Oxide Synthasementioning
confidence: 99%
“…Such an association was observed earlier by others. Asakimori et al, in 2001, found a significantly higher frequency of the ecNOS 4a allele in haemodialysis patients, both non-diabetic and diabetic, and therefore suggested that the polymorphism in intron 4 of the ecNOS gene may have influence on the progression of renal disease. Wang et al, in 1999, in their study of 302 subjects with endstage renal disease and 248 healthy controls found a significantly higher frequency of the ecNOS 4a allele in patients with ESRD caused by non-diabetic primary renal diseases.…”
Section: Discussionmentioning
confidence: 95%
“…Freedman et al2000 evaluated the role of four NOS gene polymorphisms in ESRD patients and found that the a allele of the ecNOS 4 polymorphism in the NOS gene was associated with all-cause ESRD in probands and their siblings compared with healthy subjects. One study showed that the basal concentration of NO metabolites (nitrate plus nitrite) in the plasma was reduced in individuals with essential hypertension [Asakimori et al, 2001 andYilmaz et al, 2009]. Tsukada et al,1998 reported a strong association between the a allele of the ecNOS gene and the plasma NOx (nitrate and nitrite) levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations